Some aspects of the principles of sentencing / Kunna Mani Sinniah - Kunna Mani , Sinniah (1975)
Sentencing is certainly not an aspect of criminal law and justice that is peculiar and of interest to the courts alone. In fact it is one aspect of the law which has attracted not only the courts, but also the criminologists, administrators, politicians, and the public at large. Sentencing, is itself a wide topic and in this paper, it is proposed to look at certain aspects of sentencing. This paper will not delve into the pros and cons of the various theories of punishment, for this can be obtained from any book on sentencing, not will it deal in depth about the various penal measures. What is proposed to be done is a study of the actual practise of sentencing - the aims and policies behind sentencing, the criteria which influence and guide the malaysian sentencers in assessning sentence, and the way our courts view the various categories of offences that come before it.